Smog and socioeconomics: an evaluation of equity in traffic-related air pollution generation and exposure. (September 2015) - Sider, Timothy; Hatzopoulou, Marianne; Eluru, Naveen; Goulet-Langlois, Gabriel; Manaugh, Kevin
How traffic-related air pollution generation and exposure is distributed among different population groups is an important environmental justice concern. From a social equity perspective, many questions arise at the metropolitan scale. Do socially disadvantaged communities have higher exposure levels to traffic-related air pollution? Do discrepancies exist wherein neighborhoods are not exposed to levels of pollution similar to those they themselves generate? And, is there a relationship between this discrepancy and social disadvantage? These questions are examined for the Montreal Metropolitan Region through the development of an integrated transport and emissions model. Two measures of traffic-related air pollution are estimated at the traffic analysis zone level: (1) generation (average emissions per household), and (2) exposure (average residential zone concentration). A social disadvantage index is also calculated that incorporates elements of social and material deprivation. Three levels of inequity exist regarding emissions, exposure, and socioeconomics. Social disadvantage was found to have a positive relationship with exposure, meaning that the most socially disadvantaged communities tend to experience the highest levels of traffic-related air pollution. Spatial discrepancies in emission generation versus emission exposure are also present for most of the metropolitan region. Furthermore, the communities that face a double burden of greater disadvantage and higher exposure also tend to create the lowest quantities of pollution.